2022
DOI: 10.31832/smj.950632
|View full text |Cite
|
Sign up to set email alerts
|

Relation of High Sensitive Troponin-I and C-reactive Protein to Mortality in Patients with COVID-19

Abstract: Objective The aim of the present study is to investigate whether the high sensitive troponin-I (HsTrop-I) and C-reactive protein (CRP) level that measured on admission is an independent predictor of mortality in patients with coronavirus disease 2019 (COVID-19). Materials and MethodsIn this retrospective,cross-sectional and descriptive study, a total of 175 consecutive patients with confirmed COVID-19 cases were screened from November 01, 2020 to January 31, 2021. Finally, 137 eligible patients were enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Recently published data showed that COVID-19 causes hypertension (HT) in the short term period after infection [6]. Myocardial injury and acute coronary syndrome due to COVID-19 infection is also reported in case series [7][8][9]. Little is known, however, the impact of COVID-19 pandemic on cardiovascular disorders in cardiology outpatient unit.…”
Section: Introductionmentioning
confidence: 99%
“…Recently published data showed that COVID-19 causes hypertension (HT) in the short term period after infection [6]. Myocardial injury and acute coronary syndrome due to COVID-19 infection is also reported in case series [7][8][9]. Little is known, however, the impact of COVID-19 pandemic on cardiovascular disorders in cardiology outpatient unit.…”
Section: Introductionmentioning
confidence: 99%